Oil Transport Networks in Europe - I. Guliyev (Vestnik MGIMO-Universiteta)
The author examines the problems and prospects of crude oil and petroleum products transportation market on the European continent. Particular attention is paid to the possibilities of the planned pipeline routes and new supplies of oil and petroleum products. European Union countries have large reserves of hydrocarbons, but it is not enough to fully satisfy domestic consumption. Improved pipeline infrastructure both within the EU and oil pipelines from other countries is an important economic and social factor. Recent developments of this year especially emphasize the importance of strengthening the energy security in the foreign policy of the state. For transporting fuel energy in Europe used the following types of transport: marine (sea and river), truck, railway, and pipeline. It seems necessary to mention the fact that the role of pipeline transport is particularly high in the oil and gas industry. Pipeline transport has an important impact on the formation and developmen t of the fuel and energy complex of the state, as well as regions, as its integral part. An effective system of crude oil and petroleum products pipelines is an important tool for the implementation of public policies, policies at the EU level, allowing the country to regulate the supply of crude oil and petroleum products to the overseas and domestic markets.